2014
DOI: 10.2337/db14-0746
|View full text |Cite
|
Sign up to set email alerts
|

Brown Adipose Tissue Improves Whole-Body Glucose Homeostasis and Insulin Sensitivity in Humans

Abstract: Brown adipose tissue (BAT) has attracted scientific interest as an antidiabetic tissue owing to its ability to dissipate energy as heat. Despite a plethora of data concerning the role of BAT in glucose metabolism in rodents, the role of BAT (if any) in glucose metabolism in humans remains unclear. To investigate whether BAT activation alters whole-body glucose homeostasis and insulin sensitivity in humans, we studied seven BAT-positive (BAT+) men and five BAT-negative (BAT−) men under thermoneutral conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
572
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(607 citation statements)
references
References 37 publications
26
572
2
7
Order By: Relevance
“…In conclusion, although the level of functional BAT is inversely correlated with adiposity in humans (36,37) and positively correlated with improved insulin sensitivity and glucose metabolism in mice and humans (38)(39)(40), our results suggest that reduced BAT function alone may be insufficient for the development of obesity or insulin resistance. Moreover, specific inhibition of adipose tissue G s α signaling seems to dramatically affect whole-body glucose metabolism in the absence of an effect on body weight.…”
Section: Discussionmentioning
confidence: 60%
“…In conclusion, although the level of functional BAT is inversely correlated with adiposity in humans (36,37) and positively correlated with improved insulin sensitivity and glucose metabolism in mice and humans (38)(39)(40), our results suggest that reduced BAT function alone may be insufficient for the development of obesity or insulin resistance. Moreover, specific inhibition of adipose tissue G s α signaling seems to dramatically affect whole-body glucose metabolism in the absence of an effect on body weight.…”
Section: Discussionmentioning
confidence: 60%
“…Studies have shown that an increased amount of BAT is associated with weight loss in obese subjects, and increased brown fat cell differentiation leads to an increase in energy consumption and reduction in body weight gain and diet-induced obesity (5)(6)(7). BAT also regulates glucose homeostasis and improves insulin sensitivity (8,9), and brown adipogenesis is suppressed in human subjects with insulin resistance (10). Hence, stimulating brown fat formation could be a novel route to fight against obesity and related metabolic disorders (11).…”
mentioning
confidence: 99%
“…below thermoneutrality [86] (Figure 5). In humans, acute cold exposure activates BAT especially around the neck and in the supraclavicular area (reviewed in [4]) and increases energy expenditure in proportion to BAT activation [87], [88]. Using PET it has been shown that cold stimulates activation of BAT and increases fatty acid oxidation in this depot, but not in skeletal muscle or subcutaneous adipose tissue [88].…”
Section: Browning Of Wat As a Possible Aid To Fight Metabolic Diseasesmentioning
confidence: 99%
“…The same authors studied the effects of mild cold stimulation (18°C) on dietary fatty acid (DFA) tissue extraction and oxidation in non-cold-acclimated men; after a standard liquid meal containing the long-chain fatty acid PET tracer FTHA, they observed that fractional (not total) DFA extraction in BAT was much greater than in skeletal muscle or white adipose tissue [109]. Chondronikola et al [87] showed that 5-8 h cold exposure increases whole-body energy expenditure, glucose homeostasis, and insulin sensitivity and that prolonged cold exposure stimulates genes associated with lipolysis but only in BAT and not in WAT when compared to thermoneutral conditions [110], although whole body lipolysis, FFA oxidation and TG-FFA cycling were all increased. Taken together these results suggest that BAT, despite its small size, might play a role in whole body lipid metabolism and postprandial lipid handling, if not directly at least indirectly.…”
Section: Activation Of Bat For the Improvement Of Lipid And Glucose Mmentioning
confidence: 99%